Evidence for alterations of the glial syncytial function in major depressive disorder. (January 2016) - Medina, Adriana; Watson, Stanley J.; Bunney, William; Myers, Richard M.; Schatzberg, Alan; Barchas, Jack; Akil, Huda; Thompson, Robert C.
Abstract: Background: Glial cells are essential in maintaining synaptic function. In glutamatergic synapses astrocytes remove the products of neural activity, (i.e. potassium, glutamate and excess water) from the synaptic cleft and redistribute them across the glial network; these products of neural activity can then be recycled for neuronal use or released into the vascular compartment. This type of highly coupled cell network -or syncytium-maintains the balance of synaptic activity by restoring the basal levels of such molecules in the synaptic cleft. Previous studies have reported alterations of glia related genes in Major Depressive Disorder, including some genes related to syncytial function. Methods: We used RNA isolated from hippocampal tissues of 13 MDD subjects and 10 healthy controls to broadly examine gene expression using microarrays. Hippocampal RNA samples were isolated by laser capture microdissection from human tissue sections carefully avoiding contamination from neighboring structures. Once RNA quality was validated RNA was labeled and hybridized to microarrays. Results: Analysis of microarray data identified mRNA transcripts involved in glial syncytial function that were downregulated in MDD subjects compared to controls, including potassium and water channels (KCNJ10, AQP4), gap junction proteins (GJA1) and glutamate transporters (SLC1A2, SLC1A3). These gene expression differences were confirmed by qPCR. Conclusions: The downregulation of these genes related to the syncytial network activity of glial cells is consistent with the hypothesis that synaptic homeostasis is disrupted thereby disrupting hippocampal synaptic function in MDD patients. Such glial gene expression changes could contribute either to the onset or perpetuation of depressive symptoms and hence, represent targets for novel therapeutics. Graphical abstract: Highlights: Astrocytes remove the products of neural activity and redistribute them across the glial network. Such syncytium activity maintains balanced levels of neuroactive molecules in the synaptic cleft. Downregulation genes related to the syncytial network activity of glial cells occurs in MDD. This contributes to the onset or perpetuation of depressive symptoms. The products of downregulated genes constitute novel therapeutic targets.